Partial acetylation in situ of cellulosic fabric and its resistance to microbial and actinic degradation - Maheshwari, K. L.; Gupta, U. S.; Nigam, S. S.; Bhandari, N. D. (Defence Science Journal, 2014)
Partial acetylation in situ of cotton fabrics can be achieved satisfactorily when it is carried out using 0.03 percent perchloricacid as the catalyst at a temperature not exceeding 30DegreeC. Increase in concentration of perchloric acid or temperature adversely affects the tensile strength of the fabrics. The acetylation of fabrics confers resistance to leaching. Scouring of the fabric prior to acetylation does not materially influence the extent of substitution of hydroxyl groups by acetyl ones. The acetylating mixture can be repeatedly used but fresh addition of the catalyst is necessary. With increase in the period of acetylation or in the quantity of catalyst, there is a progressive increase in acetic acid yield but the tensile strength of the fabric shows a corresponding decrease. Partial acetylation affords protection against microbial attack when the acetyl content of the acetylated fabrics is 14-15 percent. The treatment does not however afford protection against degradation by artificial light, or sunlight or weathering.